2015
DOI: 10.1002/aelm.201500090
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Pyroresistive All‐Organic Infrared Bolometer

Abstract: when processed as thin fi lms. [ 14,15 ] An alternative method to register the surface temperature of an object is a direct-contact measurement using simple paste-on temperature sensors, such as a thermistor or a thermocouple. [ 7 ] These devices provide more accurate temperature values compared to noncontact approaches, but their response time is too slow for the needs in the emerging fi eld of fast temperature sensors. [ 16 ] In this regard, the development of all-organic infrared bolometers able to operate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…[32,33] In sharp contrast to bolometers, [34] which typically show wavelength independent response and are based on local heating of the sensing element, the operation of photodetectors is based on the photoeffect, [35] inducing electronic transitions to higher energy levels and the generation of mobile charge carriers. Photo detectors based on organic semiconductors have been shown previously.…”
Section: Low-voltage Transistors For Sensorsmentioning
confidence: 99%
“…[32,33] In sharp contrast to bolometers, [34] which typically show wavelength independent response and are based on local heating of the sensing element, the operation of photodetectors is based on the photoeffect, [35] inducing electronic transitions to higher energy levels and the generation of mobile charge carriers. Photo detectors based on organic semiconductors have been shown previously.…”
Section: Low-voltage Transistors For Sensorsmentioning
confidence: 99%
“…1) which can be used both as a direct-contact thermometer and as a passive noncooled infrared sensor [4]. This sensor is capable of identifying even negligible temperature changes with accuracy of 0.005 degree [4]. The obtained results improve those obtained from widely used thermistors: the accuracy of a Pt-1000 detector is 0.01 degree [28].…”
Section: Introductionmentioning
confidence: 95%
“…It should be noted that one of the important areas for innovation in the field of organic electronics is sensing [2]. For example, it was shown that some of organic molecular conductors, such as trihalides of bis(ethylenedithio)tetrathiafulvalene (BEDT-TTF), are able to give electronic devices extraordinary strain, pressure and temperature sensing properties impossible to achieve with metal-based electronic structures, enabling a broad range of innovative "out-of-thebox" applications [3,4,5,6]. On the other hand, the attraction of (BEDT-TTF) 2 Hal 3 -organic molecular conductors is the ability to directly impact the sensing properties of the material when deposited in thin film form [3,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations